HUBUNGAN ISLAM DAN NEGARA MENURUT PEMIKIRAN ALI ABDUR RAZIQ - Nurdiani, Nurdiani (Fakultas Agama Islam, 2019)
Ali Abd Raziq's thesis is very shocking Islamic politics which proves that pure spiritual Muslims do not support politics, meaning religion and separate world affairs. Furthermore, Abd Raziq rejects the Caliphate system is not an inseparable part of Islam. According to him the Caliphate was only a matter of custom and not from Islamic law. Abd Raziq's view, according to Islamic thinkers, is very reprehensible because it has damaged the essence of Islam. According to them, the prophetic mission encompasses all life not only spirituality but also concerns politics and for them there is nothing between religion and the political order of life (world). Thus the prophetic mission can be implemented. To deny this, Ali Abdur Raziq implicitly asked for a review of the purpose of the downfall of the Prophet Muhammad or in other words it is necessary to study the basics of Islam.